Gadolinium-based contrast agents: What we learned from acute adverse events, nephrogenic systemic fibrosis and brain retention - Bäuerle, Tobias; Saake, Marc; Uder, Michael (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Radiologists have been administering gadolinium-based contrast agents (GBCA) in magnetic resonance imaging for several decades, so that there is abundant experience with these agents regarding allergic-like reactions, nephrogenic systemic fibrosis (NSF) and gadolinium retention in the brain.
CRIS-Team WoS Importer:2021-01-22